Campo térmico e consumo de energia elétrica residencial na cidade de São Carlos-SP - Azevedo, Juliana Antunes de (Universidade Federal de São Carlos, 2010)
One of the main changes observed in cities today are the changes of the urban climate in relation to its surrounding areas. Differences in thermal field of a city may interfere in the residential energy consumption, being its study relevant, once the energy is precondition so that essential facilities and benefits of modern life can be enjoyed. From this, this work has as objective establishment of relationships between the thermal field and residential energy consumption in the city of São Carlos-SP, for different scales of approach and based on some parameters of urban morphology. In the methodology three variables were worked: the urban morphology, the climate and energy consumption. In the specific case of variable the climate, this was studied in two scales: the scale micro-scale and mesoscale. Methodological work steps were: inventory, bibliographic review, selection of control points, climate study on micro-scale (composed by substeps: climatic data processing, calculation of sky view factor, calculation of occupancy rate and index of exploitation and calculation of the vegetation index), study of climate on meso-scale (composed by substeps: estimation of radiometric temperature, calculation of the vegetation index and multicriterium analysis), study of energy consumption and finally data analysis. The results confirmed that the morphological influence on thermal field in micro-scale and meso-scale. In the microscale the exploiting index, sky view factor and average height indicated behaviors as described in the bibliography for the average, maximum and minimum temperature data, while the occupancy rate has the behavior described in the bibliography for amplitude. In meso-scale vegetation was evaluated as a factor of biggest influence on the climate. The residential energy consumption presented coherent distribution with changes in thermal field; however, this changes shall also be related to social classes of regions, since these have varying patterns of use. Regarding geoprocessing techniques used in the methodology, it was observed that the algorithms, kriging and multicriterium analysis were useful in the research, however the vegetation index, despite being simple execution, did not provided for micro-scale the desirable results.
Keywords: Engenharia urbana; Clima urbano; Energia elétrica - consumo; Campo térmico; Geoprocessamento; Morfologia Urbana; Consumo Energético Residencial; Geoprocessing; Urban morphology; Thermal field; Residential energy consumption; ENGENHARIAS